Effect Of PECS (Picture Exchange Communication System) In Developing Tamil Vocabulary Among Children With Autism (International Journal of Food and Nutritional Sciences, 2022)
Autism Spectrum Disorder (ASD) is a group of complex neuro - development disorders which are characterized by repetitive and characteristic patterns of behavior and difficulties with social communication and interaction. Some of the children with Autism are verbal or non-verbal. Before developing the communication skill, children with Autism should be trained in their Mother tongue. In Tamil Nadu, Tamil is the Regional language. Most of the digitalized Applications are in English and other forign languages. Few of them are in Tamil. PECS is the abbreviation for “Picture Exchange Communication System”. It is one of the digitalized Applications, commonly used to increase the communication skills of Children with Autism. PECS is designed in Digitalized mode in selected languages such as English, Spanish, Japanese, French, German, and Greek but is not used for Tamil . This research is based on the assessment of the language development of children with Autism in Tamil using PECS. For the present study, twenty boys and ten girls with Autism studying in Regular and Special schools in Tiruppur District were identified for the assessment. The Major finding reveals that using PECS method can be easily modified in Tamil to improveTamil speaking ability of Children with Autism.